x 3 *cos(x)
d / x \ --\3 *cos(x)/ dx
Применяем правило производной умножения:
ddxf(x)g(x)=f(x)ddxg(x)+g(x)ddxf(x)\frac{d}{d x} f{\left(x \right)} g{\left(x \right)} = f{\left(x \right)} \frac{d}{d x} g{\left(x \right)} + g{\left(x \right)} \frac{d}{d x} f{\left(x \right)}dxdf(x)g(x)=f(x)dxdg(x)+g(x)dxdf(x)
f(x)=3xf{\left(x \right)} = 3^{x}f(x)=3x; найдём ddxf(x)\frac{d}{d x} f{\left(x \right)}dxdf(x):
ddx3x=3xlog(3)\frac{d}{d x} 3^{x} = 3^{x} \log{\left(3 \right)}dxd3x=3xlog(3)
g(x)=cos(x)g{\left(x \right)} = \cos{\left(x \right)}g(x)=cos(x); найдём ddxg(x)\frac{d}{d x} g{\left(x \right)}dxdg(x):
Производная косинус есть минус синус:
ddxcos(x)=−sin(x)\frac{d}{d x} \cos{\left(x \right)} = - \sin{\left(x \right)}dxdcos(x)=−sin(x)
В результате: −3xsin(x)+3xlog(3)cos(x)- 3^{x} \sin{\left(x \right)} + 3^{x} \log{\left(3 \right)} \cos{\left(x \right)}−3xsin(x)+3xlog(3)cos(x)
Теперь упростим:
3x(−sin(x)+log(3)cos(x))3^{x} \left(- \sin{\left(x \right)} + \log{\left(3 \right)} \cos{\left(x \right)}\right)3x(−sin(x)+log(3)cos(x))
Ответ:
x x - 3 *sin(x) + 3 *cos(x)*log(3)
x / 2 \ 3 *\-cos(x) + log (3)*cos(x) - 2*log(3)*sin(x)/
x / 3 2 \ 3 *\log (3)*cos(x) - 3*log (3)*sin(x) - 3*cos(x)*log(3) + sin(x)/